Analisis Potensi Interaksi Obat Pada Resep Pasien Hipertensi Lansia di Puskesmas Dabatan Misool Selatan, Raja Ampat - Nurul Maghfirah1; Lukman Hardia; Angga Bayu Budiyanto (Universitas Pahlawan Tuanku Tambusai, 2026)
Elderly people with hypertension generally receive combination therapy to control blood pressure and manage comorbidities, so they are at risk of experiencing potential drug interactions. This study aims to analyze the potential for drug interactions in the prescriptions of elderly hypertension patients at the South Dabatan Misool Health Center, Raja Ampat Regency. Methods this study was a non-experimental observational study with a retrospective descriptive approach. The research sample used a total sampling technique of 130 prescriptions of elderly hypertension patients who met the inclusion criteria. Data were obtained from prescriptions and medical records, then analyzed descriptively based on the type of interaction, mechanism, and severity. Results the majority of patients were aged 60–65 years (53.85%) and were female (80.00%). Of the 130 prescriptions, 47 cases of potential drug interactions were found. The most common combination was amlodipine–simvastatin in 14 cases (29.79%), followed by amlodipine–mefenamic acid in 11 cases (23.40%). Most interactions were pharmacodynamic interactions of moderate severity, while major interactions were found in amlodipine–simvastatin and captopril–allopurinol combinations. Conclusion the potential for drug interactions in elderly hypertensive patients at the South Dabatan Misool Health Center is quite high, so it is necessary to screen drug interactions and evaluate therapy regularly to improve the safety and effectiveness of treatment.